Sildenafil ameliorates oxidative stress and DNA damage in the stenotic kidneys in mice with renovascular hypertension - Dias, Ananda T (BioMed Central, 2014)
BACKGROUND: Oxidative stress and DNA damage have been implicated in the pathogenesis of renovascular hypertension induced by renal artery stenosis in the two-kidney, one-clip (2K1C) Goldblatt model. Considering our previous report indicating that the chronic blockade of phosphodiesterase 5 with sildenafil (Viagra®) has marked beneficial effects on oxidative stress and DNA damage, we tested the hypothesis that sildenafil could also protect the stenotic kidneys of 2K1C hypertensive mice against oxidative stress and genotoxicity. METHODS: The experiments were performed with C57BL6 mice subjected to renovascular hypertension by left renal artery clipping. Two weeks after clipping, the mice were treated with sildenafil (40 mg/kg/day for 2 weeks, 2K1C-sildenafil group) or the vehicle (2K1C). These mice were compared with control mice not subjected to renal artery clipping (Sham). After hemodynamic measurements, the stenotic kidneys were assessed using flow cytometry to evaluate cell viability and the comet assay to evaluate DNA damage. Measurements of intracellular superoxide anions and hydrogen peroxide levels as well as nitric oxide bioavailability were also obtained. RESULTS: Sildenafil treatment significantly reduced mean arterial pressure (15%), heart rate (8%), intrarenal angiotensin II (50%) and renal atrophy (36%). In addition, it caused a remarkable decrease of reactive oxygen species production. On the other hand, sildenafil increased nitric oxide levels relative to those in the nontreated 2K1C mice. Sildenafil treatment also significantly reduced the high level of kidney DNA damage that is a characteristic of renovascular hypertensive mice. CONCLUSIONS: Our data reveal that sildenafil has a protective effect on the stenotic kidneys of 2K1C mice, suggesting a new use of phosphodiesterase 5 inhibitors for protection against the DNA damage observed in the hypoperfused kidneys of individuals with renovascular hypertension. Further translational research is necessary to delineate the mechanisms involved in the prevention of renal stenosis in the clinical setting.